ROLE OF SMART TECHNOLOGY IN ARCHITECTURE-PAVING THE WAY FOR SMART FACTORY BUILDING IN KARACHI - Humaira Nazir; Dr. Ubaid Ullah; Bushra Khan; Hassaan Bilal Rashid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The concept of "smart buildings" is used to improve efficiency in the interior and exterior of a building, and it helps in providing services to the user according to the space requirement. The goal of this study is to propose a strategy for energy-efficient smart industrial buildings in Karachi that takes into account the building envelope, low energy for cooling, and appropriate electrical appliances. The study was conducted in Karachi, Sindh, Pakistan, because of its status as a "hub of industrial activities." Mixed research methods, both quantitative and qualitative, have been used to gather and analyze data, evaluate outcomes, and draw conclusions. A physical questionnaire survey was used to obtain the data. A detailed survey of the two existing factories and an analysis of the architectural planning of one factory building were carried out. In addition, Autodesk Revit was used for simulating the data and analyze the use of energy efficiently with operative temperature for thermal comfort. Findings from surveys and interviews indicated that the lack of efficient indoor environmental quality, lack of natural ventilation, inappropriate use of materials, and insufficient space planning resulted not only in suffocation and chronic illness in enclosed spaces like packaging and production areas but also increased energy consumption. Concluding, factory space is not a space designed for machines, but human needs and comfort should be considered in designing a factory. Smart building is a new norm that is being adopted for many building types around the globe, and results of simulation indicated that smart building guarantees minimum use of energy for cooling and maintaining a comfortable indoor environment for the user.